Biology Learning Content Analysis on Aves Diversity: A Case Study at Kaduberureum Biodiversity Park’s PT Chandra Asri Petrochemical Tbk, Indonesia - Pipit Marianingsih; Mahrawi Mahrawi; Adira Cahyani; Riesta Octoviani; Syifa Nurrohmah; Lailli Sabta Nugraha; Yoseph Sugiharto Karahayon; Eren Putra Febrio (International Journal of Biology Education Towards Sustainable Development, 2023)
Biology learning must be delivered contextually, for example, by presenting content based on field facts related to biodiversity. One of the biodiversity conservation areas in Banten Province is Kadubeureum Biodiversity Park, as a form of PT Chandra Asri's contribution to environmental conservation. The biodiversity park acts as a protected area for flora and fauna species found in the area, including Aves. The existence of Aves affects the quality of an environment because Aves are an important component of the ecosystem. This study aims to analyze biology content based on Aves diversity in the Kadubeureum Biodiversity Park to be implemented as contextual learning material, especially in the biodiversity concept. The research was conducted in July-November 2022. The method used was a survey and case study, completed with the point count method for Aves data collection in Biodiversity Park’s PT Chandra Asri at Kadubeureum Village, Serang, Banten, Indonesia. Based on the research identified 28 species of Aves including to 17 families. The results showed that there were several species of Aves endemic to Java, such as the "Javan Bondol" (Lonchura leucogastroides), the "Mountain Pijantung" (Arachnothera affinis), the "Paok Pancawarna" (Hydrornis guajanus), and the "Java Cinenen" (Orthotomus sepium). Furthermore, the facts obtained based on the Aves diversity observation can be used as contextual biology learning content, in the concept of biodiversity, such as for classification, biodiversity level, as well as threats and conservation effort learning.